2019
DOI: 10.1007/978-3-030-19115-3_26
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Adoption of an Integrated Hospital Information System in Rural Uganda: A Case of Kisiizi Hospital

Abstract: Electronic Medical Records (EMRs) have been proposed to improve the quality of services in healthcare organisations. However, sometimes, the design contexts of these systems tend to be different from the use contexts. This and other factors have been reported to cause failures of EMR adoptions. By focusing on factors from the Unified Theory of Acceptance and Use of Technology (UTAUT) model, we use interviews and questionnaire as data collection instruments to study the adoption of an EMR which was locally deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Chetley, Davies, Trude, McConnell, and Ramirez (2006) observed the importance of ICT in the implementation of health care systems in developing countries similar to the finding observed in developed countries. Recent literature shows that e-Health is the part of ICT which contributes toward the improvement of health care systems in developing nations (Baryashaba, Musimenta, Mugisha, & Binamungu, 2019;Hossain et al, 2019). Developing countries are also adopting ICT due to well-documented patient benefits for the solution of access, cost, and quality problems of health care.…”
Section: Introductionmentioning
confidence: 99%
“…Chetley, Davies, Trude, McConnell, and Ramirez (2006) observed the importance of ICT in the implementation of health care systems in developing countries similar to the finding observed in developed countries. Recent literature shows that e-Health is the part of ICT which contributes toward the improvement of health care systems in developing nations (Baryashaba, Musimenta, Mugisha, & Binamungu, 2019;Hossain et al, 2019). Developing countries are also adopting ICT due to well-documented patient benefits for the solution of access, cost, and quality problems of health care.…”
Section: Introductionmentioning
confidence: 99%
“…However, the research showed that the most widely used frameworks for eHealth adoption in developing countries were the Technology Acceptance Model (TAM) ( [18], [13], [23], [22], [23]), the Unified Theory of Acceptance and Use of Technology (UTAUT) ( [11], [20], [25], [30], [34]) and the Technology, Organisation and Environment (TOE) framework ( [11], [31], [28], [31], [35]).…”
Section: Review Of the Frameworkmentioning
confidence: 99%